Renal effects of NO‐inhibition in patients with cirrhosis vs. healthy controls: a randomized placebo‐controlled crossover study. (28th June 2013) - Bech, Jesper N.; Aagaard, Niels K.; Pedersen, Robert S.; Sorensen, Tina B.; Vilstrup, Hendrik; Pedersen, Erling B.
Abstract Background Nitric oxide (NO) is an important regulator of renal hemodynamics and sodium excretion. Systemic and splanchnic NO‐synthesis is increased in liver cirrhosis contributing to the characteristic hyperdynamic circulation. The significance of renal NO in human cirrhosis is not clear. Aims In order to clarify the role of NO in the regulation of renal hemodynamics and sodium excretion in human cirrhosis, we studied the effects of NG‐monomethyl‐L‐arginine (l‐NMMA) – a nonselective NO‐inhibitor – on blood pressure (MAP), heart rate (HR), GFR, RPF, UNa × V, FENa, FELi and plasma levels of renin, angII, aldo, ANP, BNP and cGMP in 13 patients with cirrhosis (Child gr.A: 8; Child gr.B+C: 5) and 13 healthy controls. Methods The study was randomized and placebo‐controlled. Renal hemodynamics were assessed by measuring renal clearance of 51Cr‐EDTA and 125I‐Hippuran for GFR and RPF, respectively. Results l‐NMMA induced a similar, significant increase in MAP in both groups and a more pronounced relative decrease in HR in the CIR group (P = 0.0209, anova). l‐NMMA did not change GFR in any group, but RPF decreased significantly in both groups, but most pronouncedly in CIR (P = 0.0478, anova). FENa decreased significantly in both groups after l‐NMMA, but the response was again most pronounced in the CIR group (P = 0.0270, anova). All parameters remained stable after placebo. No significant differences were observed between the effects of l‐NMMA in Child gr.A vs. Child gr. B+C patients. Conclusion The data supports the hypothesis that renal NO is enhanced in human cirrhosis.